Teatralização e carnavalização : a manipulação fotográfica de David Lachapelli - Spagnol, Eliane (2015)
This paperwork proposes an investigation about photo manipulation. During the research it is intended to study and reflect about these photos as a mean of contemporary artistic expression and current photographic language, which is not only focused on cap